Visualization of synaptic vesicle dynamics with fluorescence proteins - Li, Wang; Geng, Chunyang; Liu, Bo (Folia Neuropathologica, 2018)
Synaptic vesicle (SV) will be transported to the bouton along the axon, once it is formed in a cell body. After docking in the active zone, neurotransmitters will be released upon the stimulation, and then transmission of chemical signals will be initiated. Presently, many advanced technologies and burgeoning molecular sensors are being used to explore the synaptic transmission. These studies provide a new sight into the presynaptic structure and its function. The present review summarizes the application of fluorescent proteins (FPs) for SV tracking and recycling. Some FPs and relevant imaging technologies such as fluorescence resonance energy transfer (FRET), fluorescence recovery after photobleaching (FRAP) and fluorescence lifetime imaging microscopy (FLIM), are introduced here. In addition, some examples are also analyzed to visualize the dynamics of SVs in living cells with the help of some FPs.